Cholesterol biosynthesis inhibitor RO 48-8071 reduces progesterone receptor expression and inhibits progestin-dependent stem cell-like cell growth in hormone-dependent human breast cancer cells - Liang Y; Goyette S; Hyder SM (Breast Cancer: Targets and Therapy, 2017)
Yayun Liang,1,2,* Sandy Goyette,1,2,* Salman M Hyder1,2 1Department of Biomedical Sciences, 2Dalton Cardiovascular Research Center, University of Missouri, Columbia, MO, USA *These authors contributed equally to this work Abstract: Clinical trials and studies have shown that postmenopausal women undergoing combination hormone replacement therapy containing estrogen and progestin have an increased risk of breast cancer compared with women taking estrogen or placebo alone. Using animal models, we have previously shown that synthetic progestins, including medroxyprogesterone acetate (MPA), which is widely used clinically, accelerate breast cancer tumor growth and promote metastasis. Furthermore, we have found that MPA elevates CD44 protein expression and aldehyde dehydrogenase (ALDH) activity, two markers of cancer stem cells (CSCs), and increases mammosphere formation, another hallmark of stem cells, in hormone-dependent T47-D human breast cancer cells. Herein, we show that RO 48-8071 (RO), an inhibitor of cholesterol synthesis, reduced MPA-induced CD44 protein expression in two hormone-dependent human breast cancer cell lines, T47-D and BT-474. Because we have previously shown that MPA induction of CD44 is progesterone receptor (PR) dependent, we examined RO’s effects on PR protein and mRNA expressions in T47-D cells. PR mRNA levels remained unchanged after RO treatment; however, RO significantly reduced the protein expression of both PR receptor isoforms, PR-A and PR-B. Using the proteasome inhibitor MG-132, we demonstrated that RO decreases PR protein expression in T47-D cells via the proteasomal degradation pathway. Importantly, treatment of T47-D cells with RO abolished MPA-induced mammosphere formation. Based on our observations, we contend that RO may represent a novel means of preventing MPA-induced CSC expansion. RO could be used clinically to both treat and prevent hormone-dependent breast cancers, which represent the majority of human breast cancers. RO may also have clinical utility in reducing resistance to antihormone therapy. Keywords: breast cancer, cholesterol biosynthesis inhibitor, RO 48-8071, medroxyprogesterone acetate, cancer stem cells, CD44